Optimized Infliximab Induction Predicts Better Long-Term Clinical and Biomarker Outcomes Compared to Standard Induction Dosing. Issue 5 (22nd August 2022) - Lawrence, Sally; Faytrouni, Farah; Harris, Rachel E.; Irvine, Mike; Carrion, Estefania; Scott, Gregor; Clarke, Benjamin; Garrick, Vikki; Curtis, Lee; Gervais, Lisa; Tayler, Rachel; Riou, Marliss; et al.
Abstract : Objectives: To evaluate the efficacy of standard and optimized infliximab induction dosing in attaining corticosteroid (CS) free clinical remission at week 52 and the effect that post-induction trough levels have on long-term outcome. Methods: Inflammatory bowel disease (IBD) patients ≤18 years commenced on infliximab between August 1, 2016, and August 1, 2018, from Vancouver, Canada, and Glasgow, Scotland, were included. The Glasgow cohort followed standard induction while the Vancouver cohort undertook induction optimization based on clinical, biomarker, and proactive infliximab trough levels. Baseline characteristics and laboratory values were documented. Results: In total, 140 children were included [median age 14.1 years (interquartile range (IQR) 12.0–16.0)]; 54% male. CS-free clinical remission at week 52 was higher in the optimized group compared to the standard cohort [65/78 (83%) vs. 32/62 (52%), P < 0.001]. Combined CS-free clinical and biomarker remission (CRP < 5 mg/L) was also higher in the optimized compared to the standard cohort [65/78 (83%) vs 25/62 (40%), P < 0.001]. The median post-induction trough level was higher in children who were in CS-free clinical remission at week 52 [3.6 mg/L (1.5-7.1)] vs. those who were not [2.0 mg/L (0.8–4.1), P = 0.04]. The odds of attaining a therapeutic post-induction trough level were almost 4-fold higher in the optimized group than the standard cohort (OR 3.97, 95% CI: 1.89–8.68, P < 0.001). Conclusions: Standard infliximab induction resulted in less favorable long-term outcomes for pediatric IBD patients. Optimizing induction using clinical, biomarker, and proactive trough levels resulted in higher post-induction trough levels and a greater odds of attaining long-term clinical remission.